2014
DOI: 10.1099/mic.0.082263-0
|View full text |Cite
|
Sign up to set email alerts
|

LdrP, a cAMP receptor protein/FNR family transcriptional regulator, serves as a positive regulator for the light-inducible gene cluster in the megaplasmid of Thermus thermophilus

Abstract: LdrP (TT_P0055) (LitR-dependent regulatory protein) is one of the four cAMP receptor protein (CRP)/FNR family transcriptional regulators retained by the extremely thermophilic bacterium Thermus thermophilus. Previously, we reported that LdrP served as a positive regulator for the light-induced transcription of crtB, a carotenoid biosynthesis gene encoded on the megaplasmid of this organism. Here, we showed that LdrP also functions as an activator of the expression of genes clustered around the crtB gene under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…he LitR (light-induced transcription regulator)/CarH family is a MerR family of transcriptional regulatory proteins that contain a cobalamin (Cbl; synonym, vitamin B 12 )-binding domain at the C terminus (1)(2)(3)(4). The first observation regarding the involvement of vitamin B 12 in the light-inducible carotenoid (Crt) production of the Gram-negative gliding bacterium Myxococcus xanthus was presented by Cervantes and Murillo (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…he LitR (light-induced transcription regulator)/CarH family is a MerR family of transcriptional regulatory proteins that contain a cobalamin (Cbl; synonym, vitamin B 12 )-binding domain at the C terminus (1)(2)(3)(4). The first observation regarding the involvement of vitamin B 12 in the light-inducible carotenoid (Crt) production of the Gram-negative gliding bacterium Myxococcus xanthus was presented by Cervantes and Murillo (5).…”
mentioning
confidence: 99%
“…In vivo and in vitro studies showed that LitR directly binds to the intergenic promoter region of litR and crtB to repress bidirectional transcription under dark conditions. Light irradiation causes the inactivation of LitR, which in turn allows the expression of LdrP, directly activating the transcription of the crt biosynthesis gene cluster and the genes adjacent to litR (2). Interestingly, litR, cobalamin biosynthe-sis, and other light-inducible genes, including the crt genes, were all found to be located on the large plasmid of this organism (2).…”
mentioning
confidence: 99%
“…19 The photoreceptor proteins were first discovered in the bacterium Myxococcus xanthus, 6,[18][19][20] which turns red in the presence of light, as a result of the synthesis of carotenoids, but is pale yellow in the dark. However, carotenoids have also been found in a variety of other bacteria, including Streptomyces coelicolor [21][22][23] , Thermus thermophilus [24][25][26] and Bacillus megaterium 27 . Homologous sequences to the photoreceptor protein are found in the genomes of many bacteria and these proteins are probably widely distributed in non-photosynthetic bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Homologous sequences to the photoreceptor protein are found in the genomes of many bacteria and these proteins are probably widely distributed in non-photosynthetic bacteria. 6,17,19,22,25,26 The photoreceptor proteins were named CarH in M. xanthus 20 , TtCarH 25 or LitR 24 in T. thermophilus and LitR 27 in B. megaterium, but, for simplicity, and because the photoreceptor proteins are all very similar, in this review I shall use the designation CarH for the protein and carH for the gene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation